2022
DOI: 10.3390/jcm11041068
|View full text |Cite
|
Sign up to set email alerts
|

Cholestatic Liver Disease and Pregnancy: A Systematic Review and Meta-Analysis

Abstract: Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are two types of chronic cholestatic liver disease (CCLD). Little is known regarding the relationship between these conditions and pregnancy. We performed a systematic review and meta-analysis regarding the maternal and fetal outcomes amongst patients with a known diagnosis of PBC and PSC undergoing pregnancy. Our analysis shows that patients with PBC and PSC who undergo pregnancy are at an increased risk of pre-term delivery, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…If true, this further supports our argument for preeclampsia-associated liver dysfunction versus true hepatic decompensation as the etiology of acute hepatic dysfunction in the present case. While the postpartum course of secondary biliary cirrhosis is unknown, there is a higher risk of biochemical disease flare for primary biliary cholangitis and other cholestatic liver diseases in the postpartum period compared with pregnancy [ 19 , 20 ]. Meanwhile, liver damage in preeclampsia is characterized by hepatocellular damage [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…If true, this further supports our argument for preeclampsia-associated liver dysfunction versus true hepatic decompensation as the etiology of acute hepatic dysfunction in the present case. While the postpartum course of secondary biliary cirrhosis is unknown, there is a higher risk of biochemical disease flare for primary biliary cholangitis and other cholestatic liver diseases in the postpartum period compared with pregnancy [ 19 , 20 ]. Meanwhile, liver damage in preeclampsia is characterized by hepatocellular damage [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory tests revealed: hemoglobin 13.4 g/dl (12,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)5); platelet 164000/mm 3 (150000-400000); White blood cells 6720/mm 3 (4000-1000), ALAT 420UI/L (0-35) and ASAT 147UI/L (0-35), total bilirubin 72mg/l (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and direct bilirubin at 4,8mg/l (0-2); alkaline phosphatases 192UI/L (30-120 ); ɤ-glutamyl transferase 76UI/L (0-38); prothrombin level at 100%; correct albumin. Bile acid testing returned to 48.4µmol /l (<8).…”
Section: Patient and Observationmentioning
confidence: 99%
“…10 Several studies show that maternal complications do not increase in patients with PBC during pregnancy. [11][12][13] Today, there is no standard treatment for PSC. Therapeutic trials with ursodeoxycholic acid (UDCA) have shown that it improves pruritus as well as biological parameters.…”
Section: Patient and Observationmentioning
confidence: 99%